PENGARUH KUANTITAS DAN KUALITAS SUSTAINABILITY DISCLOSURE TERHADAP INNATE DAN DISCRETIONARY EARNINGS QUALITY - Kristia, Elsa; Septiani, Aditya (Diponegoro Journal of Accounting, 2019)
The purpose of this study is to examine the effect of quantity and quality of sustainability disclosure on innate and discretionary earnings quality. The sustainability disclosure quantity is measured using the GRI G4 index, while the quality of sustainability disclosure is measured based on the report form, the adherence level and external statements. Innate and discretionary earnings quality as the dependent variable are measured using a modified Jones Model. The control variables used in this study are return on assets, leverage, net operating assets, and operating cycle. The research sample consisted of 10 main sector companies, namely the agriculture and mining sub-sectors, which are listed in the Indonesia Stock Exchange in 2014-2016. The sampling method used is purposive sampling. The analysis technique in this study is multiple linear regression analysis. The findings show that sustainability disclosure quantity has a significant positive effect on innate earnings quality and does not have a significant positive effect on discretionary earnings quality. While the quality of sustainability disclosure has a significant positive effect on both innate earnings quality discretionary earnings quality.